L’agentivité des femmes morphinomanes au xixe siècle - Zoë Dubus (Genre, Sexualité et Société)
The concept of agency is very significantly an unthought of the issue of female drug use. Consulting the bibliographies or different search engines on the topic will make it possible to be convinced of this: first, and more generally, it is clear that the subject of psychotropic drugs is still mainly treated from the point of view of addiction. When the study looks – rarely – at female consumption, the topic addressed will almost inevitably focus on two poles: prostitution and the management of maternity. In order to go beyond this admittedly important but particularly restrictive diptych, we will attempt in this study to apply the notion of the capacity to act to female morphine addicts of the 19th century, who constitute the first “type” category of drug addicts in contemporary history.